EP881 Neoadjuvant chemotherapy for newly diagnosed ovarian cancer: a single center experience. (1st November 2019) - Kaparelou, M; Zakopoulou, R; Tsiara, A; Kyriazoglou, A; Liontos, M; Tsironis, G; Koutsoukos, K; Zagouri, F; Vlachos, D; Thomakos, N; Haidopoulos, D; Rodolakis, A; et al.
Abstract : Introduction/Background: Ovarian cancer (OC) is one of the most lethal gynecological malignancies. Primary Debulking Surgery (PDS) followed by chemotherapy has been the standard of care. However, two randomized trials have demonstrated that Neoadjuvant Chemotherapy(NACT) followed by Interval Debulking Surgery(IDS) is not inferior to PDS. Therefore, we conducted a retrospective analysis to determine patterns of practice in our institution. Methodology: Medical records of women with epithelial OC treated at Alexandra Hospital from 2011 to 2016 were retrospectively identified. Clinicopathological data, treatment and survival data were analyzed. Kaplan-Meier Survival curves were generated using IBM SPSS version 20; survival differences were estimated using the long-rank test. Results: 198 patients were identified. Median age was 60.8 years. 169 patients had serous carcinoma, 10 clear cell, 10 endometrial, 3 mucous and 4 adenocarcinoma. 171 had advanced (stage III/IV) disease. PDS was performed in 128 patients, while 70 received NACT. 48 performed IDS, while 6 had LDS. No surgery was performed in 16 patients. With a median follow-up of 27.3 months, mPFS was 21.8 months and mOS was 58.5 months. Patients treated with NACT-IDS had statistical significant shorter mPFS and mOS than those treated with PDS (PFS: 16.2 m vs 25.9 m P<0.001 and OS 44.4 m vs Not Reached, P=0.05). NACT-IDS retained its statistical significance as an adverse prognostic factor in multivariate analysis when controlled for stage, grade and histology of the disease (P=0.003). No statistical significant difference in the percentage of patients with platinum resistant disease among PDS and IDS was identified. Conclusion: NACT followed by IDS is frequently used in the treatment of ovarian cancer patients in a tertiary centre in Greece and was correlated with adverse outcome. A selection bias favoring NACT for patients with high risk for perioperative morbidity may affect the results of this retrospective analysis. Large randomized trials to address this issue are underway. Disclosure: Nothing to disclose.